2024
DOI: 10.1002/ana.26879
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Endovascular Thrombectomy in Acute Basilar Artery Occlusion with Low PC‐ASPECTS: A Nationwide Prospective Registry‐Based Study

Jun Young Chang,
Ji Sung Lee,
Wook‐Joo Kim
et al.

Abstract: ObjectiveWe evaluated the efficacy of endovascular thrombectomy (EVT) on the functional outcome of patients with acute basilar artery occlusion and low posterior circulation acute stroke prognosis early computed tomography score (PC‐ASPECTS).MethodsWe identified patients with acute ischemic stroke due to basilar artery occlusion and PC‐ASPECTS of 6 or less, presenting within 24 h between August 2008 and April 2022. The primary outcome was a favorable functional outcome, defined as a modified Rankin Scale (mRS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…In the same study, mRS 4-6 was observed in 46% and 88%, respectively. A very recent Korean study suggested some potential benefit of EVT in patients with low pc-ASPECTS 45 based on the inverse probability of treatment weighting model for mRS score of 0-3 (33% vs. 24%, p=0.03), but not based on propensity-score matching for the same outcome. For mRS score of 0-2, no difference was observed in any of the models.…”
Section: Additional Informationmentioning
confidence: 99%
“…In the same study, mRS 4-6 was observed in 46% and 88%, respectively. A very recent Korean study suggested some potential benefit of EVT in patients with low pc-ASPECTS 45 based on the inverse probability of treatment weighting model for mRS score of 0-3 (33% vs. 24%, p=0.03), but not based on propensity-score matching for the same outcome. For mRS score of 0-2, no difference was observed in any of the models.…”
Section: Additional Informationmentioning
confidence: 99%